PROGRAM INDUKSI DAN ORIENTASI KARYAWAN BARU SECARA VIRTUAL DI MASA PANDEMI COVID-19 PT TELKOM INDONESIA (PERSERO) TBK - Taufiq Dwi Apriyanto (Magister Administrasi Publik, FISIP, 2021)
COVID-19 has potential to change the culture. The COVID-19 crisis has forced virtual working to become the main method of doing business in the modern due to social restrictions such as PT Telkom Indonesia. Management in PT Telkom Indonesia is faced with the problem of how to keep the orientation program during the COVID-19 pandemic because the company really needs these new employees so that business processes can continue to run smoothly. This virtual orientation program does not reduce orientation values, participants can still survive, thus adding many new experiences because all assignments are made online. The point is that participants can still carry out their normal activities because technology is getting more sophisticated. This paper uses a qualitative research approach. Data collection techniques are made in two ways, field studies and literature studies. Field studies were made by interview. Orientation program are not easy because participants and companies only meet virtually. Companies should overprepare. Companies can make detailed guidelines for the implementation of the Orientation Program, make a priority scale, and always provide feedback as soon as possible on the final result. The advantages of this virtual induction program are (1) the company can save costs; (2) shorter event time; (3) safe from COVID-19 (4) the application of New Technology based on Virtual Meeting. The weakness of this virtual orientation program is (1) lack of control from mentors; (2) minimal experience for employees because material that should require meeting physically is not well conveyed, one of which is increasing collaboration between teams.